2002
DOI: 10.1246/cl.2002.1222
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Fluorescence of Pyridine-N-alkyl carbazole Copolymer Prepared by Oxidative-coupling Reaction

Abstract: A new kind of copolymers incorporated pyridine and N-alkyl carbazole alternatively into main chain has been prepared by oxidative-coupling copolymerization. The polymers are thermostable, highly soluble, and processable. The fluorescence spectra of the polymers display blue light emitting properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The main peaks on the spectra are attributed to a π→π* transition, and the shoulders correspond to n→π* transitions in the respective materials. A comparison of the photophysical properties of the synthesized polymers may be made with structurally related polymers previously synthesized by Zheng et al [21,28] . The observed differences in the absorption spectra of both polymer series arise due to the difference in alkyl chain lengths.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main peaks on the spectra are attributed to a π→π* transition, and the shoulders correspond to n→π* transitions in the respective materials. A comparison of the photophysical properties of the synthesized polymers may be made with structurally related polymers previously synthesized by Zheng et al [21,28] . The observed differences in the absorption spectra of both polymer series arise due to the difference in alkyl chain lengths.…”
Section: Resultsmentioning
confidence: 99%
“…Zheng et al have prepared a new class of copolymers that incorporate pyridine and N -alkyl carbazole alternatively into the main chain by oxidative-coupling copolymerization. These polymers are thermostable, highly soluble, and processable, and the fluorescence spectra of the polymers display blue light emitting properties [21]. …”
Section: Introductionmentioning
confidence: 99%
“…The investigation of the elongation at break revealed that the polymers PUU 2 , PUU 3 and PUU 4 presented comparable values, the highest value of elongation at break was associated with PUU 3 , which contained a molar ratio DAPy/DBDI of 2/3.15 (table 4, figure 1). In the case of PUU 1 that contained PTMG, DAPy and MDI at a molar ratio of 1/1/2, the weakest mechanical property values were observed.…”
Section: Mechanical Behaviormentioning
confidence: 98%
“…Mechanical tests including the stress-strain data and the load-unload cycles at constant rate of extension, with measurement of hysteresis and strain recovery were performed for this series of polyurethane-ureas containing pyridine rings. The results of the stress-strain measurements are given in table 4.…”
Section: Mechanical Behaviormentioning
confidence: 99%
See 1 more Smart Citation